Revitalization Of Strengthening Students’ Religious Literacy Through The Development Of Women’s Fiqh Study - Khoirul Ismah; Uswatun Chasanah; Ayep Rosidi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study examines a religious literacy learning model based on women’s fiqh with the integration of digital literacy in vocational education at SMK Islam Sudirman 1, Ambarawa. The study focuses on strengthening students’ understanding of menstruation, postpartum bleeding, and istihāḍah (non-menstrual bleeding) as essential aspects of women’s worship practices. Initial observations indicate that students’ understanding remains limited to basic rules without a deeper explanation of biological conditions and their implications for religious practice. A descriptive qualitative approach with a case study design was employed. There were 33 informants, consisting of a principal, two Islamic Religious Education teachers, and 30 female students from grades X–XII. Data were collected through classroom observation, in-depth interviews, and documentation over a two-month implementation period. Data analysis was conducted thematically through stages of data organisation, interpretation, and meaning construction. The findings reveal improvements in five dimensions of religious literacy: cognitive, analytical, affective, psychomotor, and epistemic. Students demonstrate a better ability to explain legal foundations, distinguish biological conditions, and determine worship practices more accurately. The integration of menstrual cycle tracking applications and digital fiqh texts supports access to reliable religious references. Supporting factors include school policy support, the presence of female teachers, dialogic learning approaches, and the availability of digital learning resources. Limiting factors include restricted access to technological devices, student fatigue, and initial discomfort when discussing sensitive topics.